Investigating the Relationship between Calcium Score in Coronary Arteries and Aortic Valve in Predicting the Risk of Cardiovascular Events on Cardiac Computed Tomography Angiography - Seyed Kamaledin Hadei; Mina Azhand; Farnaz Fariba (پزشکی بالینی ابن سینا)
Background and Objective: Coronary artery and aortic valve calcium measurement is a low-cost, fast, and without the need for injection of contrast media, which is important in determining the severity of atherosclerosis and the prognosis of heart disease. In this regard, this study aimed to assess the relationship between coronary artery calcium score and aortic valve calcification in order to predict the risk of cardiovascular diseases. Materials and Methods: This descriptive/cross-sectional study was conducted on 300 patients suspected of having coronary artery stenosis, candidates for coronary computed tomography (CT) angiography, who were selected via convenience and consecutive sampling methods. In CT angiography before the injection of contrast material, the calcium score in the coronary vessels and aortic valve were measured and graded according to Agatston criteria. Moreover, 3-mm chest sections were used to calculate the calcium score using the Siemens 128 CT scanner software. Data analysis was performed using SPSS software (version 26), and Spearman's correlation coefficient was employed to determine the correlation between coronary artery calcium score and aorta. Results: A positive and significant correlation was found between aortic and coronary artery calcium scores (r=0.383, P<0.001). Moreover, body mass index, hypertension, and dyslipidemia were correlated with aortic and coronary artery calcium scores. In addition, a significant relationship was detected between diabetes and aortic calcium score. However, aortic and coronary calcium scores demonstrated no association with gender, age, and smoking. Conclusion: The degree of aortic valve calcification is correlated with coronary artery calcification. Therefore, the aortic valve calcium score can also be used to predict the risk of atherosclerosis in the coronary arteries and cardiovascular events